THE SCOPE OF INPATIENT MORTALITY DUE TO SAFETY INCIDENTS IN DOMESTIC HOSPITALS - Naumenko, A.N.; Skaletsky, Yu.N.; Regan, M.M.; Didkovsky, V.L. (World of Medicine and Biology, 2020)
The problem of unintentional harm to patients is common in all countries, and especially in low- and middle-income countries. The article analyzes methodological approaches to assessing the levels of patient safety incidents in healthcare institutions. It has been established that more than 18 thousand patients die in Ukraine as a result of adverse events that can be prevented, which is significantly more than the number of victims of road traffic accidents and industrial accidents. The data obtained indicate the extreme urgency of the problem of unintentional harm to patients and the need for urgent measures to improve patient safety in domestic health care facilities. The purpose of the work was to assess patients’ mortality scope due to safety incidents in domestic hospitals. Were analyzed thematic scientific publications, statistical directories of the Center for Medical Statistics of the Ministry of Health of Ukraine, national reports, and analytical reviews on the state of man-made and natural safety in Ukraine.
Keywords: incident; patient safety; health care; inpatient mortality; unintentional harm